Posted by Jaylen | Middle Grades Math | 4 Responses

Curator TW
about 1 year ago

There are 3 simple steps to subtract fractions

Step 1. Make sure the bottom numbers (the denominators) are the same
Step 2. Subtract the top numbers (the numerators). Put the answer over the same denominator.
Step 3. Simplify the fraction (if needed).

jaydev mandal
about 1 year ago

To subtract two functions, subtract their outputs. For example, if f (x) = 2x - 1 and g(x) = x + 4 , then (f - g)(2) = f (2) - g(2) = 3 - 6 = - 3 . (f - g)(x) = f (x) - g(x) = (2x - 1) - (x + 4) = x - 5 .

Umang Bhambri
11 months ago

Its quite simple. Follow the below mentioned steps:
1. Take LCM (Least Common Multiple) of the denominators.
2. Modify the numerators based on that by cross-multiplication.
3. Subtract the numerators.

You have the answer.

Amrita Vijay
10 months ago

That's easy.
1. Make sure the denominators are the same. You can do this by finding out the LCM.
2. Subtract the fractions.
3. Reduce the final answer (it's up to you)

There are 3 simple steps to subtract fractions

Step 1. Make sure the bottom numbers (the denominators) are the same

Step 2. Subtract the top numbers (the numerators). Put the answer over the same denominator.

Step 3. Simplify the fraction (if needed).

To subtract two functions, subtract their outputs. For example, if f (x) = 2x - 1 and g(x) = x + 4 , then (f - g)(2) = f (2) - g(2) = 3 - 6 = - 3 . (f - g)(x) = f (x) - g(x) = (2x - 1) - (x + 4) = x - 5 .

Its quite simple. Follow the below mentioned steps:

1. Take LCM (Least Common Multiple) of the denominators.

2. Modify the numerators based on that by cross-multiplication.

3. Subtract the numerators.

You have the answer.

That's easy.

1. Make sure the denominators are the same. You can do this by finding out the LCM.

2. Subtract the fractions.

3. Reduce the final answer (it's up to you)